2019
DOI: 10.1093/cdn/nzz086
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Quantify Total Vitamin Activity: How to Combine the Contribution of Diverse Vitamers?

Abstract: This state-of-the-art review aims to highlight the challenges in quantifying vitamin activity in foods that contain several vitamers of a group, using as examples the fat-soluble vitamins A and D as well as the water-soluble folate. The absorption, metabolism, and physiology of these examples are described along with the current analytical methodology, with an emphasis on approaches to standardization. Moreover, the major food sources for the vitamins are numerated. The article focuses particularly on outlinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 121 publications
(144 reference statements)
0
26
0
1
Order By: Relevance
“…Through the years a factor of five have been used to convert content of 25-OHD3 to content of vitD3 (10,47), and also at the moment used in Food Databanks in UK and Denmark. In reviews for vitamin D in foods (7,23,48,49) and for the appropriate choice of vitamin D source for supplement (21) there are no documentation identified that content of 25-OHD3 is five times more efficient than content of vitD3.…”
Section: Dietary Intake Of Vitamin D Vitamersmentioning
confidence: 99%
See 4 more Smart Citations
“…Through the years a factor of five have been used to convert content of 25-OHD3 to content of vitD3 (10,47), and also at the moment used in Food Databanks in UK and Denmark. In reviews for vitamin D in foods (7,23,48,49) and for the appropriate choice of vitamin D source for supplement (21) there are no documentation identified that content of 25-OHD3 is five times more efficient than content of vitD3.…”
Section: Dietary Intake Of Vitamin D Vitamersmentioning
confidence: 99%
“…Since then, the chemical analytical procedure for quantification of vitD3 and vitD2 (vitD) in foods has been continuously improved and extended to include 25-OHD. For vitD, a standardized method is available, but no standardized method is available for 25-OHD in foods (7). Analytical methods for quantification of vitD and 25-OHD have been published, in which the steps in the analytical procedure today are similar as in the1960s.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations